Factors Contributing Toe-Readiness Of Smes - Lim, Chia Yan (2003)
One of the objectives of this study is to investigate the level of e-readiness of SMEs in Northern Malaysia. Another objective is to investigate the factors contributing to the e-readiness of SMEs in Northern Malaysia. Based on literature, researches, and works available, five variables are used in this study. E-readiness is the dependent variable, while infrastructure and technology, human capital, information security, organizational factors (resistance to change and top management commitment) are the independent variables.